Household income as a factor forming potential demand on the market of organic products - Shyian, Dmytro; Herasymenko, Yuliia; Ulianchenko, Nataliia; Velieva, Viktoriya; Kotelnikova, Iuliia (My University, 2021)
The purpose of the article is to analyze the situation of households in terms of income, expenditure, food quality, consumption of individual products and to assess the potential development opportunities for organic products market. Methodology / approach. The dialectical method of cognition, the systematic approach to the study of economic phenomena and processes, the monographic method (the analysis of scientific achievements of domestic and foreign scientists on the assessment of income, cost structure, quality of life) were used in the research. The abstract-logical method (for theoretical generalizations and formulation of conclusions), the economic-statistical method (when assessing the reliability of differences between groups of households), the graphic method (when constructing graphical images), correlation analysis (to make a correlation between the level of consumption of meat and meat products based on the amount of income in the households) were used among the special methods of research. To assess the actual state of affairs, the authors used data from the statistical observation regarding the level of income and expenditures of the population of Ukraine according to 2018, which was called “Anonymous microdata on the main indicators of income, expenditures and living conditions of households”. The total number of households that responded to questions about their income level was 7698 from 8051, or 95.6 %. Results. The article emphasizes that one of the important criteria for social protection is the quality of food supply in accordance with scientific norms and established standards. The income level and food consumption by households were compared. It was noted that in general the distribution of respondents in cash income levels was not considered to be normal. A clear correlation was established between the level of household income and the level of food consumption in both monetary and physical units. These differences were tested using the statistical method of t-test for comparing averages, which provided evidence of the difference between groups of households. Originality / scientific novelty. For the first time, the level of discrepancies in income and food consumption between households was assessed using the t-test method of comparison of averages, which allowed establishing statistically a significant difference between groups in these indicators. The assessment of the impact of household income on the level of expenditures and consumption of certain types of food products has been further developed with the identification of promising focus groups for consumers of organic products. Practical value / implications. The practical value of the results is that the identification of patterns allows to predict further trends in the level of consumption of certain types of food, particularly organic.
Keywords: quality and standard of living; organic farming; organic products; product quality; national health; basket of goods